Optical spectroscopy and current detection during warm-up and destruction of impurity–helium condensates - Krushinskaya, I.N.; Boltnev, R.E.; Bykhalo, I.B.; Pelmenev, A.A.; Khmelenko, V.V.; Lee, D.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
New experimental results on detection of optical spectra and ion currents during destruction of impurity–helium condensates (IHCs) have been obtained. It is shown that emission during IHC sample destruction is accompanied by current pulses, pressure peaks and temperature changes. The molecular bands of excimer molecules XeO* are assigned to molecules stabilized in films of molecular nitrogen covering the heavier cores of impurity clusters which form impurity–helium condensates.